3D/4D contrast-enhanced urosonography (ceVUS) in children – is it superior to the 2D technique? - Magdalena Maria Woźniak; Paweł Osemlak; Aikaterini Ntoulia; Halina Borzęcka; Beata Bieniaś; Agnieszka Brodzisz; Grzegorz Jędrzejewski; Anna Drelich-Zbroja; Maciej Powerski; Maciej Pech; Andrzej Paweł Wieczorek (Journal of Ultrasonography, 2018)
Background: By now, two-dimensional contrast-enhanced voiding urosonography (ceVUS) has become a well-established method for the diagnosis and treatment monitoring of vesicoureteral reflux in children, particularly after the recent approval for this application in children in the USA and in Europe. The introduction of three-dimensional static (3D) and real-time (4D) techniques with ultrasound contrast agents opens up new diagnostic opportunities for this imaging modality. Objective: To analyze whether 3D and 4D ceVUS is a superior technique compared to standard 2D ceVUS in diagnosing vesicoureteral reflux in children. Material and methods: The study included 150 patients (mean age 3.7 years) who underwent 2D and 3D/4D ceVUS for the diagnosis and grading of vesicoureteral reflux. Results: 2D ceVUS and 3D/4D ceVUS diagnosed the same number of vesicoureteral refluxes, however, there was a statistically significant difference in grading between the two methods. Performing 3D/4D ceVUS resulted in changing the initial grade compared to 2D ceVUS in 19 out of 107 refluxing units (17.76%) diagnosed. The 4D technique enabled a more conspicuous visualization of vesicoureteral reflux than the 3D technique. Conclusions: 2D ceVUS and 3D/4D ceVUS diagnosed the same number of vesicoureteral refluxes, however, there was a statistically significant difference in grading between the two methods. Thus 3D/4D ceVUS appears at least a valid, if not even a more conspicuous technique compared to 2D ceVUS.